Physiological Adaptations to Structured Aerobic and Resistance Exercise Among Sedentary Young Adults - MARK BENNETTE M. ULEP (The Bioscan, 2023)
This study examined the physiological adaptations to structured aerobic and resistance exercise among sedentary young adults at Isabela State University–Echague Campus. The increasing prevalence of sedentary behavior among university students poses significant health risks, including reduced cardiovascular fitness, poor muscular strength, and unfavorable body composition. Using a quantitative quasi-experimental pretest–posttest design, the study investigated the effects of two eight-week supervised exercise interventions on selected physiological variables. Participants were purposively selected sedentary young adults aged 18–25 years and were assigned to either an aerobic exercise group or a resistance exercise group. Physiological measures assessed before and after the intervention included cardiovascular endurance, resting heart rate, muscular strength, muscular endurance, and body fat percentage. Data were analyzed using descriptive and inferential statistics to determine within-group and between-group changes at a 0.05 level of significance. Results showed that both exercise modalities produced significant physiological improvements. The aerobic exercise group demonstrated greater gains in cardiovascular endurance and significant reductions in resting heart rate, indicating improved cardiorespiratory efficiency. In contrast, the resistance exercise group exhibited more pronounced increases in muscular strength and muscular endurance, reflecting neuromuscular and muscular adaptations. Both groups showed significant reductions in body fat percentage, suggesting improved metabolic efficiency. The study concludes that structured aerobic and resistance exercise programs are effective in improving key physiological indicators among sedentary young adults. The findings highlight the importance of incorporating both exercise modalities into university wellness and physical activity programs to address sedentary lifestyles and promote long-term health among young adults. Keywords aerobic exercise, resistance training, physiological adaptations, sedentary young adults, university wellness programs